Uma questão de interpretação: a influência do nível de escolaridade do cidadão para a compreensão do conteúdo do telejornal - Coimbra, Mayara Calácio de Sousa (2014)
This research aims to understand the extent to which the education level may interfere in the interpretation of the content of a newscast. As a reception research, the study analyzes the level of education as an influential category of the meaning negotiation process. Furthermore, we discuss the role of TV news in the light of the concept of citizenship and how the construction of meanings arising from the interpretation can contribute to developing a sense of belonging. Bringing an interdisciplinary research perspective, the education field appears not only as a methodological category, but as a study of the school teaching-learning process and social learning. The methodological tools permeate the literature and practical areas. During the analysis of data collected from interviews and a content analysis of news program from Rede Globo,Jornal Nacional, the field of social learning (inherent in human life), experience, consciousness, and culture stood out more in the receptive process more than the cognitive evolution achievable with school life, and that interpreting the news content is to ally with the process of building citizenship, since citizenship is directly related to the construction of sense of belonging that can be manifested only through social involvement.